Toxicological profiles of Carbamazepine, Gabapentin and their combination at high therapeutic doses in rat - Abdullah, Sinan Mohammed; Abdul Razak, Tariq; Al-Ani, Imad Matloub Dally; Abdualkader, Abdualrahman Mohammed (2014)
Combination therapy is an effective strategy in management of many health problems. There is some evidence which support a pharmaco-mechanistic way to antiepileptic drugs (AEDs) combination. The effectiveness of combination therapy as a treatment strategy for epilepsy and diabetic neuropathy is undergoing reassessment. This is a result of the increasing gratitude that all seizures and neuropathy pain cannot be managed by monotherapy in a significant percentage of patients, and of the development of a range of new AEDs some of these medications are well tolerated and less prone to complex pharmacokinetic drug interactions than their older generations. A combination of two antiepileptic drugs can be used when there is absence of benefit of one or two different monotherapy regimens. The main objective of this research is to investigate the unwanted effects of using high therapeutic doses in case of combination between two medications. Thirty five adult female Sprague–Dawley rats weighing 200–225 g are used in this experiment. All animals were housed in groups of 2-3 in a temperature (22±1 ºc), relative-humidity (60–70%) controlled room on a 12:12-h light/dark cycle and allowed free access to water and normal diet for rodents. Animal care complied with that stipulated by the local ethics committee. The rats were randomly divided into 5 groups of 7 animals each as follows: group 1= GBP (250mg/kg), group 2= CBZ (80 mg/kg), group 3=GBP+CBZ (250+80 mg/kg), group 4=GBP+CBZ (125+40 mg/kg), group 5= control (distilled water) (0.6 ml/day). Gabapentin (Neurontin, Pfizer, USA) was suspended in distilled water and administered 3 times daily. Carbamazepine liquid (Novartis, Switzerland) administered one times daily. Drugs were administered to rats by oral gavage method for one month. Animals from control and treated groups were sacrificed; dissected and small pieces of the liver and kidney were quickly removed, then fixed in 10% formalin. Following fixation, specimens were dehydrated, embedded, and then sectioned to 4 microns thickness. For histological examinations, sections were stained with Ehrlich Haematoxylin and Eosin. Blood samples are collected from all groups for biochemicals analysis. In conclusion, treatment with maximum therapeutic dose of GBP, CBZ and their combination may cause serious adverse effects. In spite of there is no pharmacokinetic interaction between these medications but there are many histopathological and biochemical abnormalities found in this study. Finally, combination therapies need to examine thoroughly regarding efficacy and unwanted effects to avoid any serious complications.